Pelestarian Makam Islam Tua Raja-Raja Sorkam Tapanuli Tengah - Nita Kardina Naibaho; Retno Sayekti; Nabila Yasmin (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
The Sorkam Kingdom, located in the village of Sorkam, Tapanuli Tengah Regency, possesses a highly valuable historical heritage, namely the Cultural Heritage of the Ancient Islamic Tombs of the Sorkam Kings. This tomb complex has become an important legacy to be preserved in order to maintain the identity and self-esteem of the community in the context of the evolving culture. The purpose of this research is to understand the preservation efforts for the Ancient Islamic Tombs of the Sorkam Kings and to identify various challenges faced, along with the efforts to overcome them. The research method used is qualitative descriptive, with data collection techniques involving observation, interviews, and documentation. The results of the research indicate that various efforts have been made to sustain this site. Protection is carried out through maintenance and restoration activities, while development is directed through in-depth research. The utilization of the site is conducted through scientific, religious, and tourism approaches.